Evaluation of palbociclib in oral squamous cell carcinoma and the role of PIK3CA in conferring resistance / Nur Syafinaz Zainal - Nur Syafinaz, Zainal (2019)
Lack of effective therapies remains a problem in the treatment of oral squamous cell carcinoma (OSCC), especially in patients with advanced tumors. OSCC development is driven by multiple aberrancies within the cell cycle pathway including amplification of cyclin D1 and loss of p16. Hence, cell cycle inhibitors of the CDK4/6-cyclin D axis are appealing targets for OSCC treatment. This study aimed to determine the potency of palbociclib and identify genetic features that are associated with palbociclibï¿½s response in OSCC. It was demonstrated that 80% of OSCC cell lines were sensitive to palbociclib at sub-micromolar concentrations. Palbociclib-treated cells were arrested at G1 phase with concomitant reduction of phosphorylated-Rb. Consistently, it was found that palbociclib was effective in controlling tumor growth in mice. Importantly, this study identified palbociclib-resistant cells to harbour mutations in the PIK3CA gene. Using isogenic cell lines, PIK3CA-mutant cells were shown to be less responsive to palbociclib compared to wildtype cells. Despite the reduction of RB phosphorylation upon palbociclib treatment, PIK3CA-mutant cells upregulated CDK2 and cyclin E1 suggesting this to be the mechanism underlying resistance to palbociclib. Further, it was demonstrated that the combination of PF-04691502, a PI3K/mTOR inhibitor, with palbociclib completely controlled tumor growth in mice. This study provides a rationale for the inclusion of PIK3CA testing in clinical evaluation of CDK4/6 inhibitors and suggests combination approaches for further clinical studies.